Digital Transformation and Local Community Empowerment for the Sustainable Development of Pantai Indah Layur - Kiswanto; Tri Hutami Wardoyo; Ain Hajawiyah; Caraka Hadi; Adi Umaryanto (Universitas Negeri Semarang, 2025)
The community service program at Pantai Indah Layur, Gedongmulyo Village, Lasem District, was implemented using a participatory action research approach that emphasized active involvement of local communities and tourism managers. The program was motivated by the significant coastal tourism potential that has not been supported by adequate managerial capacity, digital marketing utilization, and administrative systems. The objective of this program was to enhance the capacity of tourism managers through strengthening digital marketing skills, tourism package development, visitor database management, human resource competencies, and basic financial management. The program involved the Tourism Awareness Group (Pokdarwis) and village officials as key stakeholders. Activities were carried out through program socialization, training, field mentoring, student involvement under the Merdeka Belajar Kampus Merdeka (MBKM) scheme, and monitoring and evaluation. A total of 40 participants took part in the program. Evaluation results showed an average score of 4.24 in the “very good” category, indicating significant improvements in participants’ skills, particularly in problem-solving abilities. As a follow-up plan, partners are encouraged to consistently apply digital marketing strategies, regularly update visitor and financial databases, and further develop tourism packages through collaboration with local stakeholders and academic institutions. This program is expected to support the sustainable, community-based development of Pantai Indah Layur as a competitive coastal tourism destination.